Global biochemical profiling of fast-growing Antarctic bacteria isolated from meltwater ponds by high-throughput FTIR spectroscopy - Akulava, Volha; Tafintseva, Valeria; Blazhko, Uladzislau; Kohler, Achim; Miamin, Uladzislau; Valentovich, Leonid; Shapaval, Volha (PLOS ONE, 2024)
Fourier transform infrared (FTIR) spectroscopy is a biophysical technique used for non-destructive biochemical profiling of biological samples. It can provide comprehensive information about the total cellular biochemical profile of microbial cells. In this study, FTIR spectroscopy was used to perform biochemical characterization of twenty-nine bacterial strains isolated from the Antarctic meltwater ponds. The bacteria were grown on two forms of brain heart infusion (BHI) medium: agar at six different temperatures (4, 10, 18, 25, 30, and 37°C) and on broth at 18°C. Multivariate data analysis approaches such as principal component analysis (PCA) and correlation analysis were used to study the difference in biochemical profiles induced by the cultivation conditions. The observed results indicated a strong correlation between FTIR spectra and the phylogenetic relationships among the studied bacteria. The most accurate taxonomy-aligned clustering was achieved with bacteria cultivated on agar. Cultivation on two forms of BHI medium provided biochemically different bacterial biomass. The impact of temperature on the total cellular biochemical profile of the studied bacteria was species-specific, however, similarly for all bacteria, lipid spectral region was the least affected while polysaccharide region was the most affected by different temperatures. The biggest temperature-triggered changes of the cell chemistry were detected for bacteria with a wide temperature tolerance such Pseudomonas lundensis strains and Acinetobacter lwoffii BIM B-1558.
Keywords: Antarktis; bakterier; biokjemi; mikrobielle organismer; mikrobiologi

Antarctic Blue Ice Areas are hydrologically active, nutrient rich and contain microbially diverse cryoconite holes - Nowak, Aga; Isaksson, Elisabeth; Sunde, Øyvind; Elvevold, Synnøve; Sandven, Håkon; Moholdt, Geir; Hudson, Stephen R.; Urset, Anne; Edwards, Arwyn; Rassner, Sara M. E.; Pearce, David; Hamre, Børge; et al. (Communications Earth & Environment, 2024)
Antarctica is the coldest, windiest and least inhabited place on Earth. One of its most enigmatic regions is scoured by katabatic winds blue ice that covers 235,000 km2 of the Antarctic fringe. Here, we demonstrate that contrary to common belief, high-altitude inland blue ice areas are not dry, nor barren. Instead, they promote sub-surface melting that enables them to become “powerplants” for water, nutrients, carbon and major ions production. Mapping cryoconite holes at an unprecedented scale of 62 km2 also revealed a regionally significant resource of dissolved nitrogen, phosphorus (420 kg km−2), dissolved carbon (1323 kg km−2), and major ions (6672 kg km−2). We discovered that unlike on glaciers, creation of cryoconite holes and their chemical signature on the ice sheet is governed by ice movement and bedrock geology. Blue ice areas are near-surface hotspots of microbial life within cryoconite holes. Bacterial communities they support are unexpectedly diverse. We also show that near-surface aquifers can exist in blue ice outside cryoconite holes. Identifying blue ice areas as active ice sheet ecosystems will help us understand the role ice sheets play in Antarctic carbon cycle, development of near-surface drainage system, and will expand our perception of the limits of life.
Keywords: Antarktis; biogeokjemi; geografi; geologi; mikrobielle organismer; mikrobiologi

New cold-adapted bacteria for efficient hydrolysis of feather waste at low temperature - Smirnova, Margarita; Losada, Cristian Bolaño; Akulava, Volha; Zimmermann, Boris; Kohler, Achim; Miamin, Uladzislau; Oostindjer, Marije; Shapaval, Volha (Bioresource Technology Reports, 2023)
A novel cold-adapted bacteria Arthrobacter oryzae BIM B-1663 isolated from Antarctic green snow showed keratinase activity and efficient poultry feather degradation. A. oryzae strain degraded more than 80 % of chicken feathers within 7 days of cultivation at 25 °C. The optimal keratinase activity for A. oryzae BIM B-1663 was observed at 50 °C, both for α-keratin (44.86 U/mL) and for β-keratin (94 mU/mL). The obtained results from sulfite and thiol groups tests and Fourier transform infrared spectroscopy (FTIR) showed that A. oryzae strain has a different keratin degradation mechanism than the reference strain Bacillus licheniformis CCM 2145T. FTIR fingerprinting can be used for monitoring of feather hydrolysis as it showed distinct chemical differences in feather meal hydrolysates, retentate and permeate from A. oryzae and B. licheniformis strains.
Keywords: Antarktis; bakterier; biokjemi; kjemi; mikrobiologi

Experimental warming increases fungal alpha diversity in an oligotrophic maritime Antarctic soil - Newsham, Kevin K.; Misiak, Marta; Goodall-Copestake, William P.; Dahl, Malin Stapnes; Boddy, Lynne; Hopkins, David W.; Davey, Marie L. (Frontiers in Microbiology, 2022)
The climate of maritime Antarctica has altered since the 1950s. However, the effects of increased temperature, precipitation and organic carbon and nitrogen availability on the fungal communities inhabiting the barren and oligotrophic fellfield soils that are widespread across the region are poorly understood. Here, we test how warming with open top chambers (OTCs), irrigation and the organic substrates glucose, glycine and tryptone soy broth (TSB) influence a fungal community inhabiting an oligotrophic maritime Antarctic fellfield soil. In contrast with studies in vegetated soils at lower latitudes, OTCs increased fungal community alpha diversity (Simpson’s index and evenness) by 102–142% in unamended soil after 5 years. Conversely, OTCs had few effects on diversity in substrate-amended soils, with their only main effects, in glycine-amended soils, being attributable to an abundance of Pseudogymnoascus. The substrates reduced alpha and beta diversity metrics by 18–63%, altered community composition and elevated soil fungal DNA concentrations by 1–2 orders of magnitude after 5 years. In glycine-amended soil, OTCs decreased DNA concentrations by 57% and increased the relative abundance of the yeast Vishniacozyma by 45-fold. The relative abundance of the yeast Gelidatrema declined by 78% in chambered soil and increased by 1.9-fold in irrigated soil. Fungal DNA concentrations were also halved by irrigation in TSB-amended soils. In support of regional- and continental-scale studies across climatic gradients, the observations indicate that soil fungal alpha diversity in maritime Antarctica will increase as the region warms, but suggest that the accumulation of organic carbon and nitrogen compounds in fellfield soils arising from expanding plant populations are likely, in time, to attenuate the positive effects of warming on diversity.
Keywords: Antarktis; kjemi; klimaendringer; mikrobiologi; sopper

Temperature- and Nutrients-Induced Phenotypic Changes of Antarctic Green Snow Bacteria Probed by High-Throughput FTIR Spectroscopy - Smirnova, Margarita; Tafintseva, Valeria; Kohler, Achim; Miamin, Uladzislau; Shapaval, Volha (Biology, 2022)
Temperature fluctuations and nutrient composition are the main parameters influencing green snow microbiome. In this study we investigated the influence of temperature and nutrient conditions on the growth and cellular chemical profile of bacteria isolated from green snow. Chemical profiling of the green snow bacteria was done by high-throughput FTIR spectroscopy combined with multivariate data analysis. We showed that temperature and nutrients fluctuations strongly affect growth ability and chemical profile of the green snow bacteria. The size of colonies for green snow bacteria grown at higher (25 °C) and lower (4 °C and 10 °C) than optimal temperature (18 °C) was smaller. All isolates grew on rich medium, and only 19 isolates were able to grow on synthetic minimal media. Lipid and mixed spectral regions showed to be phylogeny related. FTIR fingerprinting indicates that lipids are often affected by the temperature fluctuations. Growth on different media resulted in the change of the whole chemical profile, where lipids showed to be more affected than proteins and polysaccharides. Correlation analysis showed that nutrient composition is clearly strongly influencing chemical changes in the cells, followed by temperature.
Keywords: Antarktis; bakterier; kjemi; mikrobiologi; multivariate data analysis

Microbes influence the biogeochemical and optical properties of maritime Antarctic snow - Hodson, Andrew; Nowak, Aga; Cook, Joseph; Sabacka, Marie; Wharfe, Emma S; Pearce, David Anthony; Convey, Peter; Vieira, Gonçalo (Journal of Geophysical Research: Biogeosciences, 2017)
Snowmelt in the Antarctic Peninsula region has increased significantly in recent decades, leading to greater liquid water availability across a more expansive area. As a consequence, changes in the biological activity within wet Antarctic snow require consideration if we are to better understand terrestrial carbon cycling on Earth's coldest continent. This paper therefore examines the relationship between microbial communities and the chemical and physical environment of wet snow habitats on Livingston Island of the maritime Antarctic. In so doing, we reveal a strong reduction in bacterial diversity and autotrophic biomass within a short (<1 km) distance from the coast. Coastal snowpacks, fertilized by greater amounts of nutrients from rock debris and marine fauna, develop obvious, pigmented snow algal communities that control the absorption of visible light to a far greater extent than with the inland glacial snowpacks. Absorption by carotenoid pigments is most influential at the surface, while chlorophyll is most influential beneath it. The coastal snowpacks also indicate higher concentrations of dissolved inorganic carbon and CO2 in interstitial air, as well as a close relationship between chlorophyll and dissolved organic carbon (DOC). As a consequence, the DOC resource available in coastal snow can support a more diverse bacterial community that includes microorganisms from a range of nearby terrestrial and marine habitats. Therefore, since further expansion of the melt zone will influence glacial snowpacks more than coastal ones, care must be taken when considering the types of communities that may be expected to evolve there.
Keywords: Antarktis; biogeokjemi; mikrobiologi; mikroorganismer; snøalger; snøpakke; snøsmelting

Some like it cold: microbial transformations of mercury in polar regions - Barkay, Tamar; Kroer, Niels; Poulain, Alexandre J (Polar Research, 2011)
The contamination of polar regions with mercury that is transported from lower latitudes as inorganic mercury has resulted in the accumulation of methylmercury (MeHg) in food chains, risking the health of humans and wildlife. While production of MeHg has been documented in polar marine and terrestrial environments, little is known about the responsible transformations and transport pathways and the processes that control them. We posit that as in temperate environments, microbial transformations play a key role in mercury geochemical cycling in polar regions by: (1) methylating mercury by one of four proposed pathways, some not previously described; (2) degrading MeHg by activities of mercury resistant and other bacteria; and (3) carrying out redox transformations that control the supply of the mercuric ion, the substrate of methylation reactions. Recent analyses have identified a high potential for mercury-resistant microbes that express the enzyme mercuric reductase to affect the production of gaseous elemental mercury when and where daylight is limited. The integration of microbially mediated processes in the paradigms that describe mercury geochemical cycling is therefore of high priority especially in light of concerns regarding the effect of global warming and permafrost thawing on input of MeHg to polar regions. Keywords: Microbiology; mercury biogeochemistry; redox transformations; polar regions; methylation
Keywords: Antarktis; biogeokjemi; forurensning; mikrobiologi; miljøvern; polarområdene; økosystemer

Meteoritten som vitnet om liv på Mars - Knutsen, Henning; Matland, Aleksander (Naturen, 2011)
Har livet på Jorda blitt ført hit fra tidligere liv på planeten Mars? I 1996 hevdet en gruppe forskere at en meteoritt fra Mars faktisk inneholdt spor etter organisk liv. Hvis dette virkelig var tilfelle, ville det medføre en revolusjon for vårt syn på verden og det univers vi befinner oss i. Men vitenskapsfolk besitter sunn skepsis, og hos dem kommer ikke tvilen tiltalte til gode. Nå mener de fleste ekspertene at funnet var for godt til å være sant.
Keywords: Antarktis; astrofysikk; mikrobiologi

Using fluorescence to characterize dissolved organic matter in Antarctic sea ice brines - Stedmon, Colin A; Thomas, David N; Papadimitriou, Stathys; Granskog, Mats A; Dieckmann, Gerhard S (Journal of Geophysical Research: Biogeosciences, 2011)
Sea ice plays a dynamic role in the air-sea exchange of CO2. In addition to abiotic inorganic carbon fluxes, an active microbial community produces and remineralizes organic carbon, which can accumulate in sea ice brines as dissolved organic matter (DOM). In this study, the characteristics of DOM fluorescence in Antarctic sea ice brines from the western Weddell Sea were investigated. Two humic-like components were identified, which were identical to those previously found to accumulate in the deep ocean and represent refractory material. Three amino-acid-like signals were found, one of which was unique to the brines and another that was spectrally very similar to tryptophan and found both in seawater and in brine samples. The tryptophan-like fluorescence in the brines exhibited intensities higher than could be explained by conservative behavior during the freezing of seawater. Its fluorescence was correlated with the accumulation of nitrogen-rich DOM to concentrations up to 900 μmol L−1 as dissolved organic carbon (DOC) and, thus, potentially represented proteins released by ice organisms. A second, nitrogen-poor DOM fraction also accumulated in the brines to concentrations up to 200 μmol L−1 but was not correlated with any of the fluorescence signals identified. Because of the high C:N ratio and lack of fluorescence, this material is thought to represent extracellular polymeric substances, which consist primarily of polysaccharides. The clear grouping of the DOM pool into either proteinaceous or carbohydrate-dominated material indicates that the production and accumulation of these two subpools of DOM in sea ice brines is, to some extent, decoupled.
Keywords: Sørishavet; Weddellhavet; fluorescens; gassutveksling; havis; karbondioksid; marin økologi; mikrobielle organismer; mikrobiologi; sjøis

Telonema antarcticum sp. nov., a common marine phagotrophic flagellate - Klaveness, Dag; Shalchian-Tabrizi, Kamran; Thomsen, Helge Abildhauge; Eikrem, Wenche; Jakobsen, Kjetill S. (International Journal of Systematic and Evolutionary Microbiology, 2005)
Telonema is a widely distributed group of phagotrophic flagellates with two known members. In this study, the structural identity and molecular phylogeny of Telonema antarcticum was investigated and a valid description is proposed. Molecular phylogeny was studied using small-subunit rRNA (SSU rRNA) gene sequences. The pear-shaped cell had two subequal flagella that emerged laterally on the truncated antapical tail. One flagellum had tripartite hairs. The cell was naked, but had subsurface vesicles containing angular paracrystalline bodies of an unknown nature. A unique complex cytoskeletal structure, the subcortical lamina, was found to be an important functional and taxonomic feature of the genus. Telonema has an antero-ventral depression where food particles are ingested and then transferred to a conspicuous anterior food vacuole. The molecular phylogeny inferred from the SSU rRNA gene sequence suggested that Telonema represents an isolated and deep branch among the tubulocristate protists.
Keywords: Sørishavet; Weddellhavet; fylogenetikk; marin biologi; mikrobiologi

Isolation and partial characterization of a parapoxvirus isolated from a skin lesion of a Weddell seal - Tryland, M.; Klein, J.; Nordøy, E.S.; Blix, A.S. (Virus Research, 2005)
A solitary skin lesion was found on the neck of a Weddell seal (Leptonychotes weddellii), chemically immobilized in Queen Maud Land (70°09′S, 05°22′E) Antarctica 2001. The lesion was elevated and 3cm in diameter, consisting of partly fresh and partly necrotic tissue, and proliferative papilloma-like structures were seen. Electron microscopy on a biopsy from the lesion revealed typical parapoxvirus particles. Polymerase chain reaction (PCR; B2L gene) generated amplicons of approximately 594 base pairs, comparable to Orf-virus, the prototype parapoxvirus. A comparison of these B2L PCR amplicon DNA sequences with corresponding sequences from other parapoxviruses, showed that the Weddell seal virus resembled isolates from grey seal (Halichoerus grypus) and harbour seal (Phoca vitulina) more than parapoxvirus from red deer (Cervus elaphus), sheep, cattle and Japanese serows (Capricornis crispus). It is thus concluded that the Weddell seal parapoxvirus belong to the tentative seal parapoxvirus species. Since parapox and orthopoxviruses may cause similar clinical diseases, we suggest that the term sealpox should be restricted to the clinical disease, whereas seal parapoxvirus should be used when caused by a parapoxvirus, rather than the general term “sealpox virus”. This is the first verified case of parapoxvirus infection in a Weddell seal, and also the first report of any such infections in the Antarctic.
Keywords: Dronning Maud Land; Weddellhavet; fylogenetikk; marin biologi; mikrobiologi; pinnipedier; seler; virologi

Selv under ekstreme betingelser har man liv, finnes det også liv utenfor jorda? - Brunfelt, Arild O (Naturen, 2002)
Livets opprinnelse er et mysterium. Ikke desto mindre er mange forskere beskjeftiget med å forsøke og rekonstruere dette. Moderne forskning på livet under ekstreme betingelser på Jorda som f.eks. i dyphavet, i en innsjø under isen i Antarktis eller i en gruppe sjeldne meteoritter, har ført til en viss optimisme når det gjelder å finne liv på planeten Mars og på Jupiters månesatelliter Europa, Callisto og Ganymede.
Keywords: Antarktis; kjemiske analyser; mikrober; mikrobiologi; subglasial innsjø

Effect of isolation temperature on the characteristics of extracellular proteases produced by Antarctic bacteria - Vazquez, Susana C; Mac Cormack, Walter P (Polar Research, 2002)
Protease-producing psychrotolerant bacteria were isolated from Antarctic biotopes on casein agar plates using different incubation temperatures. Most of the isolates were non-spore-forming Gram-negative motile rods with catalase activity, 30% were pigmented and none of them were glucose fermenters. All the strains were grown in liquid cultures at 20°C and protease secretion was tested using the azocasein method. Despite their capacity for production of a clear zone of hydrolysis in agar plates, some strains did not produce detectable levels of proteolytic activity in liquid cultures. The lowest apparent optimum temperature for protease activity found in culture supernatants was 40°C. Almost all the strains showed activation energy values about 10-20 kJ-mol?1 lower than that observed for a mesophilic Subtilisin. Most of the proteases showed optimal activity at neutral or alkaline pH values and developed a multiple-band profile on gelatine-SDS-PAGE. It was observed that the lower the strain isolation temperature was, the more stongly cold-adapted–in terms of optimal temperature and activation energy–were the proteases produced by them. This dependence of the characteristics of the proteases on the isolation temperature is an important factor to take into account in the design of screening programmes directed towards the isolation of psychrotolerant bacteria able to produce proteases strongly or weakly adapted to work in the cold. The Antarctic area explored proved to be a promising source of proteolytic bacteria with potential use in industrial processes to be carried out at low or moderate temperatures.
Keywords: Antarktis; analyser; bakterier; ekspedisjoner; mikrobiologi

Residue determinants and sequence analysis of cold-adapted trypsins - Schrøder Leiros, Hanna-Kirsti; Willassen, Nils Peder; Smalås, Arne O. (Extremophiles, 1999)
The digestive enzyme trypsin is among the most extensively studied proteins, and its structure has been reported from a large number of organisms. This article focuses on the trypsins from vertebrates adapted to life at low temperatures. Cold-adapted organisms seem to have compensated for the reduced reaction rates at low temperatures by evolving more active and less temperature-stable enzymes. We have analyzed 27 trypsin sequences from a variety of organisms to find unique attributes for the cold-adapted trypsins, comparing trypsins from salmon, Antarctic fish, cod, and pufferfish to other vertebrate trypsins. Both the "cold" and the "warm" active trypsins have about 50 amino acids that are unique and conserved within each class. The main unique features of the cold-adapted trypsins attributable to low-temperature adaptation seem to be (1) reduced hydrophobicity and packing density of the core, mainly because of a lower (Ile + Leu)/(Ile + Leu + Val) ratio, (2) reduced stability of the C-terminal, (3) lack of one warm trypsin conserved proline residue and one proline tyrosine stacking, (4) difference in charge and flexibility of loops extending the binding pocket, and (5) different conformation of the "autolysis" loop that is likely to be involved in substrate binding.
Keywords: Sørishavet; biokjemi; fisker; marin biologi; mikrobiologi; polarområdene

Microbial communities from the sea ice and adjacent water column at the time of ice melting in the northwestern part of the Weddell Sea - Mathot, Sylvie; Becquevort, Sylvie; Lancelot, Christiane (Polar Research, 1991)
Keywords: Sørishavet; Weddellhavet; alger; bakterier; diatomeer; havis; mikrobiologi; protozo; sjøis; smelting